Pengaruh Harga Emas Dunia, STI Index, N225 Index, KS11 Index, DJI Index, terhadap IHSG dan Dampaknya pada Indeks IDX30 Bursa Efek Indonesia (2012-2020) - I Made Adnyana; Andini Nurwulandari; Suryadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study analyzes the influence of the World Gold Price, STI Index, N225 Index, KS11 Index, DJI Index, on the IHSG and its Impact on the IDX30 Index of the Indonesia Stock Exchange (2012-2020). Hypothesis testing in this study used a statistical analysis tool Structural Equation Modeling (SEM). The results showed that the World Gold Price had a positive and insignificant effect on the IHSG, the STI Index had a negative and significant effect on the IHSG, the N225 Index had a positive and insignificant effect on the IHSG, the KS11 Index had a negative and significant effect on the IHSG and the DJI Index had a positive and insignificant effect. against the IHSG. The World Gold Price has a negative and significant effect on IDX30, the STI Index has a positive and significant effect on IDX30, the N225 Index has a negative and significant effect on IDX30, the KS11 Index has a positive and significant effect on IDX30 and the DJI Index has a positive and insignificant effect on IDX30. World Gold Price has insignificant effect on IDX30 through IHSG, STI Index has insignificant effect on IDX30 through IHSG, N225 Index has insignificant effect on IDX30 through IHSG, KS11 Index has insignificant effect on IDX30 through IHSG and DJI Index has insignificant effect on IDX30 through IHSG. IHSG has a positive and significant effect on IDX30.